Where Are the Women Architects? - Stratigakos, Despina (Book collections on Project MUSE., 2016)
"For a century and a half, women have been proving their passion and talent for building and, in recent decades, their enrollment in architecture schools has soared. Yet the number of women working as architects remains stubbornly low, and the higher one looks in the profession, the scarcer women become. Law and medicine, two equally demanding and traditionally male professions, have been much more successful in retaining and integrating women. So why do women still struggle to keep a toehold in architecture? Where Are the Women Architects? tells the story of women's stagnating numbers in a profession that remains a male citadel, and explores how a new generation of activists is fighting back, grabbing headlines, and building coalitions that promise to bring about change. Despina Stratigakos's provocative examination of the past, current, and potential future roles of women in the profession begins with the backstory, revealing how the field has dodged the question of women's absence since the nineteenth century. It then turns to the status of women in architecture today, and the serious, entrenched hurdles they face. But the story isn't without hope, and the book documents the rise of new advocates who are challenging the profession's boys' club, from its male-dominated elite prizes to the erasure of women architects from Wikipedia. These advocates include Stratigakos herself and here she also tells the story of her involvement in the controversial creation of Architect Barbie. Accessible, frank, and lively, Where Are the Women Architects? will be a revelation for readers far beyond the world of architecture."--